Physical Quality of Broiler Chicken Meat Added with Banana Weevil Enriched ?-glucan from Saccharomyces cerevisiae in Feed - Imam, Shokhirul; Suryadi, Ujang; Hanafi, Muhammad Ilham (Universitas Veteran Bangun Nusantara, 2023)
This study aims to determine the effect of adding banana weevil flour enriched with ?-glucan fiber from Saccharomyces cerevisiae to feed on the physical quality of broiler meat. The research method used a completely randomized design and analysis of variance, this study used 200 DOC consisting of 5 treatments and 4 replications. Each replication contains 10 chickens. The level of ?-glucan administration from Saccharomyces cerevisiae with banana weevil flour was P0 (control); P1 (25 ppm); P2 (50 ppm); P3 (75 ppm); and P4 (100 ppm). The treatment started from 16 to 37 days old. Physical quality test was carried out with thigh meat samples. Physical quality test data were analyzed by analysis of variance and if there was a significantly different (P<0.05), it was further tested with Duncan's Multiple Range Test. The results of the physical quality test on broiler chicken meat showed that the addition of banana weevil flour enriched with ?-glucan fiber from Saccharomyces cerevisiae in the feed on the physical quality of broiler meat was not significantly different (P?0.05) on the pH value, water holding capacity, reduced cooking and tenderness. The results of the study concluded that the addition of banana weevil flour enriched with ?-glucan fiber from Saccharomyces cerevisiae in feed on the physical quality of broiler meat did not affect the physical quality of broiler meat.